Anisotropic and hierarchical SiC@SiO(2) nanowire aerogel with exceptional stiffness and stability for thermal superinsulation - Su, Lei (Sci Adv, 2020)
Ceramic aerogels are promising lightweight and high-efficient thermal insulators for applications in buildings, industry, and aerospace vehicles but are usually limited by their brittleness and structural collapse at high temperatures. In recent years, fabricating nanostructure-based ultralight materials has been proved to be an effective way to realize the resilience of ceramic aerogels. However, the randomly distributed macroscale pores in these architectures usually lead to low stiffness and reduced thermal insulation performance. Here, to overcome these obstacles, a SiC@SiO(2) nanowire aerogel with a nanowire-assembled anisotropic and hierarchical microstructure was prepared by using directional freeze casting and subsequent heat treatment. The aerogel exhibits an ultralow thermal conductivity of ~14 mW/m·K, an exceptional high stiffness (a specific modulus of ~24.7 kN·m/kg), and excellent thermal and chemical stabilities even under heating at 1200°C by a butane blow torch, which makes it an ideal thermally superinsulating material for applications under extreme conditions.